The industrial novels : Charlotte Brontë's Shirley, Charles Dickens' Hard times and Elizabeth Gaskell's North and South /: Charlotte Brontë's Shirley, Charles Dickens' Hard times and Elizabeth Gaskell's North and South. (2015) - Balkaya, Mehmet Akif
No abstract available